PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK, PAIR, SHARE (TPS) DALAM PEMBELAJARAN SENI TARI KELAS VII 3 DI SMP NEGERI 31 PADANG - Eldira Fragus Shinta; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2015)
Abstract   The objective of the study was to describe planning, activities, and increasing of study result with using the cooperative learning model typed “Think, Pair, Share” in studying of dancing at class VII 3 SMP 31 Padang. Study typed was study of classroom action research with qualitative and quantitative approaches. Amount 32 students were participated in this study. Study  results of the research cycle 1 shows the results of observation of the RPP was 82% (Good) increased to 96% (Very Good) in cycle 2. Teacher  Activities at cycle 1 was 64% (Less) increased to 89% (Very Good) in second cycle , while students activity cycle 1 was 66% (enough) increased to 89% (Very Good) in second cycle . cognitive Aspects of cycle 1 was 53% (less) increased to 85% (good) at second cycle . affective aspect of one cycle is 36 % (less) increased to 83% (good) cycle 1 second cycle . psychomotor aspect was 54.4% (less) increased to 88.4% (very good). The average results of student at cycle 1 was 76.8 increased to 88.18 in second cycle . Thus, by using cooperative model typed “think, pair, share” could increased the study result of Dance’s art Class VII 3 SMP N 31 Padang.   Keywords: learning outcomes, the model type cooperative think, pair, share, learning the art of dance